“Looking on darkness which the blind do see”: the Figure of the Blind Girl in Dickens and the Dickensian - Francesca ORESTANO (E-REA)
The article focuses on the theme of blindness in Dickens’s American Notes (1842) and in The Cricket on the Hearth (1845): sight impairment is treated as a vehicle to carry the reader from landscape to inscape, staging at once truth and deception, blindness and insight. Such dramatic irony is also the leitmotif of Wilkie Collins’s Poor Miss Finch (1872) and is fully acknowledged in André Gide’s La Symphonie pastorale (1919). Finally the cinema, notably Charlie Chaplin with City Lights (1932), exploits the visual drama of the blind girl whose inner vision is manipulated from the outside, yet retains the means to undo the visible deception, and grasp the essence of truth. The paradox offered by protagonists who are at once entombed in blindness and yet open books for those who see them, is present in the authors, and made more poignant and effective.